A guide to everyday economic statistics - Clayton, Gary E.; Giesbrecht, Martin Gerhard (Boston : McGraw-Hill Irwin, 1990)
Examines how different series are constructed and how we may use them effectively. This guide puts statistics in context, so the reader can see how an individual statistic relates to the larger picture.
Includes bibliographical references and index.
Keywords: Economics